Flexitarianism: Decarbonising through flexible vegetarianism - Raphaely, Talia; Marinova, Dora (Elsevier, 2014)
In a world constantly shaped by climate change, the search for decarbonising pathways will deliver many innovative technological solutions as well as trigger changes in the way people behave. This however will take time and will require negotiations and new business models. There is increasing evidence that arresting climate change at 2°C is unlikely to be attained in a world where carbon is essential for development. Achieving agreement and commitments between developed and developing countries have proven difficult but is there something that those most responsible for the current levels of CO2e emissions in the atmosphere can do? The paper examines food consumption and argues that there is a lot of potential for decarbonisation if people reduce their meat consumption. The highest levels of meat consumption are observed in the developed world and the livestock sector has been shown to be the largest single contributor for greenhouse gas emissions globally. Estimates indicate that a low-meat diet can reduce the cost of abating climate change. The paper presents an argument as to how flexitarianism e reduced meat consumption to the recommended healthy levels, can help in arresting climate change. Flexitarianism offers an easy way to achieve fast decarbonisation and has the added benefits of contributing towards improving not only the biophysical health of the planet but also that of its human habitants.